أزمة النقد في التشكيل السوري المعاصر - اشتي, شفيق; أحمد, نجوى حسين (Latakia University Journal -Engineering Sciences Series, 2019)
للنقد أهمية خاصة في علم الجمال المعاصر، فهو وسيلة تساعد الناقد على حسن تذوق العمل الفني، وتحليله، وشرحه، وتقويمه. وهو بمثابة رحلة يقوم بها المرء إلى عالم الأعمال الفنية، ويعبر عن انطباعاته الذاتية وأحكامه الجمالية بطريقة موضوعية. ولابد لتقدير العمل الفني من معايير للقيمة، كما لابد للناقد من فحص العمل ذاته، فالعمل الفني مشحون بالقيم. ولا شك بأن تغيرات عظيمة تنشأ بنتيجة التقدم العلمي والتقني في نظام أداء الأعمال الفنية لوظائفها، وكذلك قد تحسنت وسائل الإعلام، بطريقة أظهرت إمكانات ضخمة لإقامة التواصل بين الجماهير الشعبية والفن، وبالتالي فهناك تغيير جذري يطرأ على العلاقة بين الفن والمشاهد، باتجاه الغنى الفكري، والثقافي، والبصري، لذلك كان لابد من الاهتمام بأمور النقد، وإعطائها دورا فعالا، لتواكب النتاجات الفنية، وترقى بها إلى مكانة مرموقة بين فنون العالم. Criticism has special importance in the contemporary beauty science; so, it is a device that helps the critic on lovely tasting the artistic work, analyzing it, explaining it, and assessing it. It is like a journey that one is doing to the artistry businesses world expressing about its subjectivity impressions and its aestheticism rules in an objectivity way. We must estimate the artistic work from criteria to the value that artistic work is charged and the critic must examine the work itself so the artistic work is charged by values. It is no doubt that great changes are established by a result the scientific and technical progress in the performance system of the artistically works to its functions. It also has improved the media in a way that showed huge possibilities to stay communication between popularity audiences and art. There is also a radical change happening on the relation between art and spectators towards the intellectual richness. In brief, criticism is so crucial that without which coping the world art would remain a dream.